Contro l’isomorfismo. Il rapporto soggetto-oggetto secondo Enzo Melandri - Lagna, Marco; Lévano, Paulo Fernando (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
By reviewing key notions in the philosophy of Enzo Melandri regarding the topic of isomorphism, the problem of time-perception will be faced from a phenomenological standpoint; this, in order to establish in which terms it might be still useful to distinguish between one mode of temporality that is subjective (time perception) and one that is objective (time of nature). Time and its perception, as dealt with in the classical postures of Augustine and Kant, will turn useful to reveal the both ontological and gnoseological assumption that an isomorphism holds between the subject’s language and objective states of things. De-classing the isomorphism to mere “gnoseological ideology” shall ultimately lead to the acknowledgment that a theory of isomorphism is unwarranted for, and that temporality holds for every consideration of ours, whether it derives from an ontological or a gnoseological order of priorities. What holds as a correct model of reality changes as time goes by, not human knowledge having some sort of limited reach, but instead because of human knowledge always having the potentiality of become ever more precise.